2015
DOI: 10.1161/circresaha.114.305777
|View full text |Cite
|
Sign up to set email alerts
|

IRF2BP2 Reduces Macrophage Inflammation and Susceptibility to Atherosclerosis

Abstract: Rationale: Inflammation impairs macrophage cholesterol clearance from vascular tissues and promotes atherosclerosis. Inflammatory macrophages suppress expression of the transcription cofactor interferon regulatory factor 2–binding protein 2 (IRF2BP2), and genetic variants near IRF2BP2 associate with ischemic heart disease progression in humans. Objectives: To test whether IRF2BP2 in macrophages affects atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 39 publications
(33 reference statements)
6
95
0
Order By: Relevance
“…IRF2BP2-deficient macrophages have a heightened inflammatory response when challenged with lipopolysaccharides (LPS), whereas their response to interleukin-4 (IL4)-induced activation of anti-inflammatory M2 genes is impaired. Our studies further demonstrated that ablation of IRF2BP2 in macrophages worsens atherosclerosis in mice, and a deletion variant that lowers IRF2BP2 expression predisposes to coronary artery disease in humans (Chen et al, 2015). Given known differences in basal gene expression between macrophages and microglia (Hickman et al, 2013), it was important to determine whether IRF2BP2 controls microglia polarization in a similar fashion as in macrophages.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…IRF2BP2-deficient macrophages have a heightened inflammatory response when challenged with lipopolysaccharides (LPS), whereas their response to interleukin-4 (IL4)-induced activation of anti-inflammatory M2 genes is impaired. Our studies further demonstrated that ablation of IRF2BP2 in macrophages worsens atherosclerosis in mice, and a deletion variant that lowers IRF2BP2 expression predisposes to coronary artery disease in humans (Chen et al, 2015). Given known differences in basal gene expression between macrophages and microglia (Hickman et al, 2013), it was important to determine whether IRF2BP2 controls microglia polarization in a similar fashion as in macrophages.…”
Section: Introductionsupporting
confidence: 56%
“…We recently identified a novel function of IRF2BP2 as a key regulator of macrophage polarization: it promotes activation of anti-inflammatory (M2) marker genes and inhibits pro-inflammatory (M1) markers (Chen et al, 2015). Bone Marrow-derived Macrophages (BMDMs) isolated from LysMCre/IRF2BP2flox mice do not express IRF2BP2 and have impaired cholesterol handling due to their inflammatory phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage functions can vary widely depending on a number of interacting variables and factors, including local environment (“tissue niche”) (Gosselin et al, 2014; Lavin et al, 2014); intracellular energy metabolism (Van den Bossche et al, 2017); gut microbiota metabolites (Wang et al, 2011); and genetic and epigenetic factors, including non-coding RNAs (Erbilgin et al, 2013; Chen et al, 2015; Wu et al, 2016; Amit et al, 2016; Phan et al, 2017; Aryal et al, 2014). These factors program macrophages for functions on a spectrum from inflammatory and host defense to resolution and repair.…”
Section: Inflammatory Macrophages Drive Atherosclerosis Progressionmentioning
confidence: 99%
“…Although the majority of works available in the literature proposes a role for IRF2BP2 as a repressor in the regulation of diverse genes [4][5][6][7][8][9], there is some evidence that IRF2BP2 may also act as a positive regulator of gene expression [10,11]. The mechanisms by which IRF2BP2 mediates its repression or induction in the course of gene-expression regulation have not been established and may involve interaction with the DNA and/or with different proteins that vary according to the context.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this protein has been described as a participant in at least 2 distinct transcriptional repressor complexes, in which it is dependent on either its zinc finger or RING domains [8,9]. As IRF2BP2 is ubiquitously expressed and has diverse roles described in several biologic contexts [4][5][6][7][8][9][10][11], more studies are necessary to investigate its possible roles in different cell types.…”
Section: Introductionmentioning
confidence: 99%